Are human rights enough? On human rights and inequality. Issue 4 (2nd October 2021) - Jones, Charles
ABSTRACT: In this paper I respond to the central claims presented in Samuel Moyn's influential book, Not Enough: Human Rights in an Unequal World . Moyn argues that human rights have the following features: they are powerless to combat growing material inequality; they share key characteristics with neoliberalism; they make only minimalist or sufficientarian demands and therefore are not enough to achieve the equality demanded by justice. He suggests, in particular, that Henry Shue's Basic Rights exemplifies these features. My response argues that Moyn does not accurately present the core conceptual and normative characteristics of human rights, nor does he succeed in implicating Shue's conception in his critique. I suggest that Moyn's own ideas about global justice are incompletely developed, including his views about the scope, content, and distributive principles that should guide an account of global justice. Finally, I argue that, even though human rights are only part of an account of global justice, nonetheless they do provide reasons to limit socioeconomic inequality. This point is exemplified by the claim that a human right to democracy requires limits on material inequality in order to prevent power hierarchy. In short, I agree with Moyn that human rights are not enough by themselves to achieve global justice, but I reject his multi-pronged critique of human rights, specifically his claim that they imply no constraints on socioeconomic inequality.